Microneedle-Mediated Transdermal and Intradermal Drug Delivery - Donnelly, Ryan F. [et al.] (Chichester Wiley-Blackwell, 2012)
One of the latest techniques in drug delivery, microneedles are used for administering a wide range of drug substances used to treat various medical conditions. Thorough background information is included providing a history of the field.
Include Index, Illustration and References
Keywords: Microinjections -- Transdermal medication -- Drug delivery systems